Teologiczne impulsy kulturowej i społecznej emancypacji Dalitów (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Dominant theological thinking within the ecumenical movement emphasizes significance of theology and churches for the processeses of upholding more just and egalitarian social structures. According to ecumenists, theological reflection should be contextual, “from the grassroots” and referring to the given cultural, economic and social conditions. An example is the Dalit theology. It is developed by the social group who experienced, down the centuries, total social exclusion due to the Indian caste system. Article discussses the key elements of the Dalit theology, presents its context and describes its significance for the social movement of the Dalit emancipation.